2013
DOI: 10.1111/1469-0691.12199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Staphylococcus aureus strains isolated from inpatients with infected diabetic foot ulcers in an Algerian University Hospital

Abstract: Staphylococcus aureus is the most common pathogen cultured from diabetic foot infection (DFI). The consequence of its spread to soft tissue and bony structures is a major causal factor for lower-limb amputation. The objective of the study was to explore ecological data and epidemiological characteristics of S. aureus strains isolated from DFI in an Algerian hospital setting. Patients were included if they were admitted for DFI in the Department of Diabetology at the Annaba University Hospital from April 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 30 publications
12
57
1
Order By: Relevance
“…12 Moreover, recent epidemiological studies reveal that SEK is among the most prevalent superantigens in clinical isolates, particularly in methicillin resistant S. aureus (MRSA), and is thus far the only SE to be associated with CA-MRSA. 4,[13][14][15][16][17] We have previously shown that SEK was secreted by all examined S. aureus strains that encode the toxin (n D 36), and, in a murine soft-tissue infection model, we demonstrated that clinical isolates cause comparable accumulation of SEK within abscesses regardless of the amount of SEK they secrete in-vitro. 18 Here, we utilize our previously described SEK-binding mAbs to further explore the role of SEK in immune activation and disease.…”
Section: Introductionmentioning
confidence: 65%
“…12 Moreover, recent epidemiological studies reveal that SEK is among the most prevalent superantigens in clinical isolates, particularly in methicillin resistant S. aureus (MRSA), and is thus far the only SE to be associated with CA-MRSA. 4,[13][14][15][16][17] We have previously shown that SEK was secreted by all examined S. aureus strains that encode the toxin (n D 36), and, in a murine soft-tissue infection model, we demonstrated that clinical isolates cause comparable accumulation of SEK within abscesses regardless of the amount of SEK they secrete in-vitro. 18 Here, we utilize our previously described SEK-binding mAbs to further explore the role of SEK in immune activation and disease.…”
Section: Introductionmentioning
confidence: 65%
“…isolated MRSA; they found the nasal carriage of S. aureus to be significantly associated with cancer and previous hospitalization for kidney failure due to immunological suppression and hemodialysis. The MRSA isolates ST239 ( n = 60), ST80 ( n = 27), ST5 ( n = 2), ST22 ( n = 2), and ST535 ( n = 1) harbored mecA . In another study in Algeria, typing of 64 MRSA isolated from human pus ( n = 47), venous catheters ( n = 7), tracheal aspirates ( n = 4), puncture fluids ( n = 3), blood ( n = 2), and urine ( n = 1) in 64 patients found that 50 were hospital‐acquired MRSA (HA‐MRSA) and 14 were community‐acquired MRSA (CA‐MRSA); mecA , mobilized by SCC mec , was the only detected mechanism of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Several epidemiological studies have shown that sel-k is one of the most prevalent enterotoxin genes in clinical isolates of S. aureus (10,(12)(13)(14)(15)(16). Moreover, in several of these studies, SEl-K was significantly associated with CA-MRSA strains (10,15,16), which included USA300, USA400, and other clones.…”
Section: Discussionmentioning
confidence: 98%
“…One of these toxins, SEl-K, has been shown to exhibit superantigenic properties, including V␤-specific T cell activation, pyrogenicity, emesis, and lethality in primates (7)(8)(9). Epidemiological studies have demonstrated the SEl-K-encoding genes to be among the most common SE genes in S. aureus clinical isolates (10)(11)(12)(13)(14). Additionally, SEl-K is the only SE gene to our knowledge that is significantly associated with community-acquired methicillin-resistant S. aureus (CA-MRSA) strains of several clonal lineages (10,15,16).…”
mentioning
confidence: 99%